Asymptotic expansion for harmonic functions in the half‐space with a pressurized cavity. (22nd February 2016) - Aspri, Andrea; Beretta, Elena; Mascia, Corrado
Abstract : In this paper, we address a simplified version of a problem arising from volcanology. Specifically, as a reduced form of the boundary value problem for the Lamé system, we consider a Neumann problem for harmonic functions in the half‐space with a cavity C . Zero normal derivative is assumed at the boundary of the half‐space; differently, at ∂ C, the normal derivative of the function is required to be given by an external datum g, corresponding to a pressure term exerted on the medium at ∂ C . Under the assumption that the (pressurized) cavity is small with respect to the distance from the boundary of the half‐space, we establish an asymptotic formula for the solution of the problem. Main ingredients are integral equation formulations of the harmonic solution of the Neumann problem and a spectral analysis of the integral operators involved in the problem. In the special case of a datum g, which describes a constant pressure at ∂ C, we recover a simplified representation based on a polarization tensor. Copyright © 2016 John Wiley & Sons, Ltd.